DIRECT PARTICIPATION OF PEOPLE DURING REALIZATION OF JUSTICE: PROBLEMS OF THE LEGISLATIVE ADJUSTING IN UKRAINE - Prylutzkyi , Сергей Валентинович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The theoretical analysis of constitutional principles of direct participation of people is conducted during realization of justice. The legislative order of organization and activity of court opens up with participation of assessor in a people's court and jury trial. The walkthrough of regulation of forming of lists of assessor in a people's court and juror. The features of home model of «court of jurors» open up, that is entered in accordance with the new Criminal judicial code of Ukraine (2012). Drawn conclusion, that a legislator only at terminology level differentiated the forms of direct participation of people during realization of justice depending on industry of rule-making. In the field of criminal trial is a «court of jurors», in the civil justice is a court with participation of people's court and juror. At the same time, neither administrative nor economic judicial proceedings is not foreseen to some from the forms of direct participation of people during realization of justice, that limits constitutional principle of direct democracy substantially.